Zero and Net Zero Energy - Hailu, Getu (IntechOpen, 2019)
There is a growing concern about fluctuating energy prices, energy security, and the impact of climate change. Buildings are amongst the primary energy consumers in the world. This fact underlines the importance of targeting building energy use as a key to decreasing any nation's energy consumption. According to the American Society of Heating, Refrigeration and Air Conditioning Engineers (ASHRAE) Research Strategic Plan 2010-2015, even limited deployment of Net-Zero-Energy buildings within this timeframe will have a beneficial effect by reducing the pressure for additional energy and power supply and the reduction of GHG emissions. The building sector is poised to significantly reduce energy use by incorporating energy-efficient strategies into the design, construction, and operation of new buildings and retrofits to improve the efficiency of existing buildings.